Why has South Africa been relatively unsuccessful at attracting inward foreign direct investment since 1994? - Fulton, Mark Hugh John (Rhodes University, Faculty of Commerce, Department of Economics and Economic History, 2014)
Foreign Direct Investment (FDI) flows into South Africa have been very low for several decades, and this research examines the reason(s) why this has been the case since 1994. There is a common belief amongst economists that there is a positive relationship between the amount of FDI received and economic growth, thus the desire to attract greater FDI inflows. A literature review was conducted to establish the determinants of FDI globally and then data were collected and assessed to test which causes are most important. The performance of developing nations in attracting FDI was first compared with that of the developed nations. Thereafter, a regional breakdown of FDI flows was presented, with a particular focus on the Southern African region. FDI inflows to South Africa since 1994 were compared against the identified determinants of FDI, as well as with FDI inflows into two other major mining economies, Chile and Botswana. The friendliness of the government towards business was identified as a significant determinant of FDI inflows and the importance of this factor in explaining FDI inflows into environment in South Africa was looked at in more depth. It was found that many investors perceive the South African government as hostile towards business and as corrupt and/or inefficient. The empirical results show that this negative perception helps explain the FDI inflows attracted by South Africa since 1994. Therefore, increased friendliness to business by the government should increase future inward FDI flows into South Africa.
Keywords: Investments, Foreign -- South Africa; Investments, Foreign -- Africa, Southern; Investments, Foreign -- Chile; Investments, Foreign -- Botswana; Economic development -- South Africa; Economic development -- Developing countries; Political corruption -- Economic aspects -- South Africa; South Africa -- Economic policy -- 1994-